Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

Spatio‐Temporal Variation in Aerial Arthropod Abundance Revealed by Weather Radars - Mansi Mungee; Maryna Lukach; Chris Shortall; James R. Bell; Elizabeth J. Duncan; Freya I. Addison; Lee E. Brown; William E. Kunin; Christopher Hassall; Ryan R. Neely (Global Change Biology, 2025)
Arthropod declines have been reported widely; however, a lack of comprehensive data has hindered our ability to assess their large‐scale generality and drivers. Here, we used a novel and freely available dataset—atmospheric scans from a network of meteorological radars—to quantify aerial abundance of both diurnal and nocturnal arthropods across the United Kingdom, spanning different geographic regions and land cover types. Based on observations between 2014 and 2021, and across more than 35,000 km 2 , we estimate numbers of arthropods flying over the UK at heights between 500 and 700 m above ground at 1.12 (±0.01) × 10 13 individuals during the diurnal (0800–1400 UTC) and 5.02 (±0.01) × 10 12 during the nocturnal (including dusk, 1800–2200 UTC) period, showing significant spatial heterogeneity. Although spatial patterns differed, both diurnal and nocturnal arthropods increased in the south and declined mainly in the far north; on average, only nocturnal arthropods showed an overall decline. Aerial abundance of both diurnal and nocturnal arthropods showed positive relationships with woodland, grassland, and urban land cover, and negative relationships with artificial light intensity and arable land cover. Our study highlights the importance of spatial variation in temporal biodiversity trends and illustrates the need for comparative studies between nocturnal and diurnal arthropods. Notably, by extracting vertical profiles of radar reflectivity and polarization signatures, we demonstrate how weather radar datasets can be used to quantify aerial arthropod abundance, detect diurnal and seasonal activity patterns, and examine their environmental drivers across large spatial and temporal scales.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Identification and mapping of a novel resistance gene to the rice pathogen, Cercospora janseana - Christopher K. Addison; Brijesh Angira; Tommaso Cerioli; Donald E. Groth; Jonathan K. Richards; Steven D. Linscombe; Adam N. Famoso (Theoretical and Applied Genetics, 2021)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Association mapping reveals loci associated with multiple traits that affect grain yield and adaptation in soft winter wheat - Dennis N. Lozada; R. Esten Mason; Md Ali Babar; Brett F. Carver; Gina-Brown Guedira; Keith Merrill; Maria Nelly Arguello; Andrea Acuna; Lucas Vieira; Amanda Holder; Christopher Addison; David E. Moon; et al. (Euphytica, 2017)

QTL and major genes influencing grain yield potential in soft red winter wheat adapted to the southern United States - Christopher K. Addison; R. Esten Mason; Gina Brown-Guedira; Mohammed Guedira; Yuanfeng Hao; Randall G. Miller; Nithya Subramanian; Dennis N. Lozada; Andrea Acuna; Maria N. Arguello; Jerry W. Johnson; Amir M. H. Ibrahim; et al. (Euphytica, 2016)

Carry-over effects and foraging ground dynamics of a major loggerhead breeding aggregation - Simona A. Ceriani; James D. Roth; Anton D. Tucker; Daniel R. Evans; David S. Addison; Christopher R. Sasso; Llewellyn M. Ehrhart; John F. Weishampel (Marine Biology, 2015)

Tolerance of wheat to vegetative stage soil waterlogging is conditioned by both constitutive and adaptive QTL - Diana C. Ballesteros; R. Esten Mason; Christopher K. Addison; M. Andrea Acuña; M. Nelly Arguello; Nithya Subramanian; Randall Galen Miller; Haley Sater; Edward E. Gbur; David Miller; Carl A. Griffey; Marla D. Barnett; et al. (Euphytica, 2015)